Sustainable economic development: comparative analysis of Ukraine and European countries. - Filipishyna, Liliya; Pardaeva, Ozoda; Belopolsky, Mykola; Legeza, Darya; Легеза, Дар'я Георгіївна; Sarkisian, Larysa (My University, 2024)
The study analyzed key indicators of sustainable development of the economies of Ukraine and European countries. Despite the insignificant progress of Ukraine in comparison with European countries in key indicators, especially in the areas of energy efficiency and environmental protection, it is possible to note some aspects of social security in Ukraine, such as the level of education and access to medical services, show positive dynamics compared to a number of countries of the Central and Eastern Europe. Ukraine faces the challenges of war, destruction and inflation. It was determined that Ukraine remains the country with the lowest level of income per capita in Europe, with a GDP per capita of 32% of the average value of the European Union countries. The EU uses GDP indicators to allocate funds from structural funds, contributing to the development of less developed countries. Using purchasing power parity to estimate GDP helps unify the measurement of the economic potential of different countries. The study also emphasizes the importance of implementing integrated policies that would contribute to the balanced development of all three components of sustainability. In particular, the need for further integration of Ukraine into European economic and environmental initiatives is noted, which will help increase its economic competitiveness and promote sustainable development.
Сталий економічний розвиток : порівняльний аналіз України та країн Європи.